The hydration of Li+ and Mg2+ in subnano carbon nanotubes using a multiscale theoretical approach - Liu, Ruirui; Jing, Zhuanfang; Shao, Yifan; Zhou, Yongquan; Zhu, Fayan; Liu, Hongyan (Frontiers in Chemistry, 2023)
The separation of brines with high Mg/Li mass ratios still faces huge challenges. To provide a theoretical basis for the design of separation materials, the hydration of Li+ and Mg2+ in confinement using carbon nanotubes (CNTs) as the 1-D nanopore model was investigated by a multiscale theoretical approach. According to the analysis of the first coordination layer of the cations, we find that the coordination shells of two cations exist inside CNTs, and the second coordination shells of the cations are unstable. Moreover, the results of the structure analysis indicate that the hydration layer of Li+ is not complete in the CNTs with diameters of 0.73, 0.87 and 1.00 nm, yet this case does not occur in the 0.60 nm CNT, which is explained by the formation of contact ion pairs (CIP) between Li+ and Cl-, going through a unstable solvent-shared ion-pair [Li(H2O)4]+, which is extended by 400 ns in the 0.60 nm CNT to further research above results. However, the hydration layer of Mg2+ is complete and not sensitive to the diameter of CNTs by molecular dynamics simulation and ab-initio molecular dynamics (AIMD) method. Furthermore, the results of the orientation distribution of Li+ and Mg2+ indicate that the water molecules around Mg2+ are more ordered than those water molecules around Li+ in the CNTs and are more analogous to the bulk solution. We concluded that it is energetically unfavorable for confining Li+ inside the CNT with a diameter of 0.60 nm, and is favorable for confining Li+ inside the other four CNTs and Mg2+ in all CNTs, which is driven by the strong electrostatic interaction between cations and Cl-. In addition, the interaction between cations and water molecules in the five CNTs is also analyzed from the Noncovalent Interaction (NCI) perspective by AIMD.